Combined Alphavirus Replicon Particle Vaccine Induces Durable and Cross-Protective Immune Responses against Equine Encephalitis Viruses - Reed, Douglas S. (American Society for Microbiology, 2014)
Alphavirus replicons were evaluated as potential vaccine candidates for Venezuelan equine encephalitis virus (VEEV), western equine encephalitis virus (WEEV), or eastern equine encephalitis virus (EEEV) when given individually or in combination (V/W/E) to mice or cynomolgus macaques. Individual replicon vaccines or the combination V/W/E replicon vaccine elicited strong neutralizing antibodies in mice to their respective alphavirus. Protection from either subcutaneous or aerosol challenge with VEEV, WEEV, or EEEV was demonstrated out to 12 months after vaccination in mice. Individual replicon vaccines or the combination V/W/E replicon vaccine elicited strong neutralizing antibodies in macaques and demonstrated good protection against aerosol challenge with an epizootic VEEV-IAB virus, Trinidad donkey. Similarly, the EEEV replicon and V/W/E combination vaccine elicited neutralizing antibodies against EEEV and protected against aerosol exposure to a North American variety of EEEV. Both the WEEV replicon and combination V/W/E vaccination, however, elicited poor neutralizing antibodies to WEEV in macaques, and the protection conferred was not as strong. These results demonstrate that a combination V/W/E vaccine is possible for protection against aerosol challenge and that cross-interference between the vaccines is minimal. IMPORTANCE Three related viruses belonging to the genus Alphavirus cause severe encephalitis in humans: Venezuelan equine encephalitis virus (VEEV), western equine encephalitis virus (WEEV), and eastern equine encephalitis virus (EEEV). Normally transmitted by mosquitoes, these viruses can cause disease when inhaled, so there is concern that these viruses could be used as biological weapons. Prior reports have suggested that vaccines for these three viruses might interfere with one another. We have developed a combined vaccine for Venezuelan equine encephalitis, western equine encephalitis, and eastern equine encephalitis expressing the surface proteins of all three viruses. In this report we demonstrate in both mice and macaques that this combined vaccine is safe, generates a strong immune response, and protects against aerosol challenge with the viruses that cause Venezuelan equine encephalitis, western equine encephalitis, and eastern equine encephalitis.